Concess\~oes no setor de infraestrutura: Propostas para um novo modelo de financiamento e compartilhamento de riscos - Fabiano Mezadre Pompermayer; Edison Benedito da Silva Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The paper discusses the main challenges and opportunities for attracting both private domestic and foreign capital to foster the growth of concessions projects in the infrastructure sector, and proposes solutions from the Brazilian recent experience and other emerging economies. Given the exhaustion of the public funding sources in Brazil and the increasing demand for finance in the infrastructure sector in the coming decades, there is a consensus on the need of attracting private capital so to ensure the viability of the various concession projects planned for the period. We shall propose a new model for concession financing with provisions for demand risk to be shared between the Government and the concessionaire in order to increase participation of private capital in these projects. The model may also include currency hedge instruments in order to increase its attractiveness to foreign investors.
Keywords: H54; H43; O22; 330; concessions; infrastructure; project finance; risk management